Living Qur`an in Yasinan Tradition During Rabu Abeh Ritual in Gampong Lhok Pawoh, Southwest Aceh - Makmunzir, Makmunzir; Hasan, Abdur Rokhim; Lubis, Zakaria Husin; Samad, Sri Astuti A.; Sangaji, Ruslan (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article discusses an interesting phenomenon in Gampong Lhok Pawoh, where the community continues to maintain and preserve the tradition of yasinan in the Rabu Abeh ritual despite the shifting or even extinction of many religious traditions in the modern era. This research employed qualitative methods (field research) and adopted Spradley's ethnography approach and the perspective of the living Qur'an. This study aims to describe how the Qur'an comes alive in the yasinan tradition of the Rabu Abeh ritual, which is still upheld by the community of Gampong Lhok Pawoh, as well as the significance of this tradition in their daily lives. The findings reveal that the yasinan tradition in the Rabu Abeh ritual is a tangible manifestation of the living Qur'an among the people of Gampong Lhok Pawoh in Aceh Barat Daya. This tradition is performed every year on the last Wednesday of Safar, as a plea for safety and protection from potential disasters on the day of Rabu Abeh. The community perceives the connection between verse 19 of Surah Al-Qamar/54, which depicts an unfortunate day, and the Rabu Abeh day; hence, they collectively recite Surah Yasin as a prayer and safeguard against potential calamities. The tradition holds strong spiritual and social meanings within the community, serving as an effort to seek salvation from Allah SWT, preserving cultural heritage, fostering social bonds, and cultivating excellent and respectful personalities. Moreover, the tradition reminds the community of the importance of maintaining harmonious relationships with nature while strengthening solidarity and preserving customs and culture